2019
DOI: 10.1111/nyas.14002
|View full text |Cite
|
Sign up to set email alerts
|

PTPRD: neurobiology, genetics, and initial pharmacology of a pleiotropic contributor to brain phenotypes

Abstract: Receptor‐type protein tyrosine phosphatase, receptor type D (PTPRD) has likely roles as a neuronal cell adhesion molecule and synaptic specifier. Interest in its neurobiology and genomics has been stimulated by results from human genetics and mouse models for phenotypes related to addiction, restless leg syndrome, neurofibrillary pathology in Alzheimer's disease, cognitive impairment/intellectual disability, mood lability, and obsessive‐compulsive disorder. We review PTPRD's discovery, gene family, candidate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 119 publications
1
63
0
Order By: Relevance
“…Here, we analyzed the role of the tyrosine phosphatase PTPRD in NPCs during embryonic cortical development. Ptprd, the gene that encodes this protein, is associated with several neurodevelopmental disorders, including obsessive-compulsive disorder, ASDs, and intellectual disability (Choucair et al, 2015;Uhl and Martinez, 2019). We show that Ptprd is a key determinant of embryonic neurogenesis, controlling the numbers of neurogenic intermediate progenitor cells and, ultimately, the number of cortical neurons.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Here, we analyzed the role of the tyrosine phosphatase PTPRD in NPCs during embryonic cortical development. Ptprd, the gene that encodes this protein, is associated with several neurodevelopmental disorders, including obsessive-compulsive disorder, ASDs, and intellectual disability (Choucair et al, 2015;Uhl and Martinez, 2019). We show that Ptprd is a key determinant of embryonic neurogenesis, controlling the numbers of neurogenic intermediate progenitor cells and, ultimately, the number of cortical neurons.…”
Section: Discussionmentioning
confidence: 83%
“…Receptor protein tyrosine phosphatase delta (PTPRD), a member of the LAR (leukocyte common antigen-related receptor) family and a regulator of tyrosine kinase signaling, has been associated with several neural disorders (Choucair et al, 2015;Uhl and Martinez, 2019). However, its function and contribution to neural development and the pathogenesis of neural disorders has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…PTPδ has been implicated in various brain disorders, including ADHD, restless leg syndrome, addiction, bipolar disorder, obsessive–compulsive disorder, and intellectual disability (Anney et al , ; Schormair et al , ; Elia et al , ; Distel et al , ; Malhotra et al , ; Yang et al , ; Kim et al , ; Jarick et al , ; Moore et al , ; Choucair et al , ; Drgonova et al , ; Mattheisen et al , ; Uhl et al , ; Uhl & Martinez, ). Our results indicate that hyperactivity and sleep disturbances are shared by Ptprd −/− , Emx1‐Cre;Ptprd fl / fl , and Ptprd‐meA −/− mice (Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond these fundamental aspects, LAR‐RPTPs have been implicated in diverse brain disorders. In particular, PTPRD has been extensively associated with a large number of brain disorders (Uhl & Martinez, ), including attention‐deficit hyperactivity disorder (ADHD) (Anney et al , ; Elia et al , ; Distel et al , ; Jarick et al , ), restless leg syndrome (SNP study) (Schormair et al , ; Yang et al , ; Kim et al , ; Moore et al , ), addiction (Drgonova et al , ; Uhl et al , ), bipolar disorder (Malhotra et al , ), obsessive–compulsive disorder (Mattheisen et al , ), and intellectual disability (Choucair et al , ). Previous studies on Ptprd ‐mutant mice have revealed impairments in synaptic plasticity, learning, and memory (Uetani et al , ; Drgonova et al , ); dendritic arborization in cortical neurons (Nakamura et al , ); and axon targeting in motor neurons (Uetani et al , ), as well as enhanced cocaine preference and suppressed sleep‐like behaviors (Drgonova et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there is evidence for the involvement of PTPRD variants in correlated behavioral phenotypes such as loneliness, 32 temperament, 33 openness, 34 anxiety and major depression 35 . PTPRD is expressed most abundantly in brain tissue, and has a role as a neuronal cell adhesion molecule and synaptic specifier, 36 making it a good candidate for wellbeing and related behavioral traits and psychopathology.…”
Section: Discussionmentioning
confidence: 99%